Social Cognition, Language, and Prosocial Behaviors: A Multitrait Mixed-Methods Study in Early Childhood. Issue 6 (18th August 2018) - Conte, Elisabetta; Grazzani, Ilaria; Pepe, Alessandro
ABSTRACT: Research Findings : In this study, we investigated associations among social cognition skills (specifically, emotion knowledge and theory of mind), language abilities, and 3 varieties of prosocial behavior (helping, sharing, and comforting) in early childhood. The effects of age and gender were also taken into account. Participants were 149 Italian children between 24 and 47 months of age ( M  = 35.6 months, SD  = 6.77 months). We adopted a multitrait mixed-methods research design, using direct measures of emotion knowledge, theory of mind, and language as well as naturalistic observations of children's free play with peers to detect the frequency with which they engaged in prosocial behaviors. Ordinal logistic regression analyses showed that helping behaviors were especially accounted for by emotion knowledge and gender, whereas variance in sharing behaviors was mostly explained by theory-of-mind ability and language. Practice or Policy : The findings encourage those involved in early childhood education to develop training and intervention programs to enhance children's emotional, linguistic, and cognitive skills. Given that these results were obtained with children as young as 2 and 3 years, preventive intervention should be implemented during the earliest years of life.